2018
DOI: 10.5472/marumj.474194
|View full text |Cite
|
Sign up to set email alerts
|

Çocuklarda akut zehirlenme; 2015 yılında Marmara Üniversitesi Hastanesi’ne başvuran olguların değerlendirilmesi

Abstract: Objectives: According to Turkish Statistical Institute (TurkStat), 6477 children aged between 1 and 17 years, died in 2015 and 29.5% (n=1909) of these deaths were because of injuries due to external causes and poisoning. Our aim is to produce solutions to this problem by evaluating demographics, clinical features of patients and the causes and consequences of poisoning. Materials and Methods: The hospital medical records of children who were admitted with acute intoxication to Pediatric Emergency Service at Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…2,17,23,24 In our study, the most common cause of non-pharmaceutical poisoning was corrosivecaustic substances, in line with the recent studies conducted in Turkey. 3,25 In the second place, poisoning with detergents came forth. Esophageal injury should be considered after poisoning with corrosive-caustic substances.…”
Section: Discussionmentioning
confidence: 99%
“…2,17,23,24 In our study, the most common cause of non-pharmaceutical poisoning was corrosivecaustic substances, in line with the recent studies conducted in Turkey. 3,25 In the second place, poisoning with detergents came forth. Esophageal injury should be considered after poisoning with corrosive-caustic substances.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common sources of intoxication, after multiple drug intake and corrosive poisoning, is tricyclic antidepressants (TCAs). [2][3][4][5] Methods commonly used by adolescents for purposes of suicide include hanging, exhaust fume inhalation, and medication overdoses including acetaminophen, benzodiazepines, and TCAs. [6][7][8] Intoxications caused by the TCA amitriptyline are very important because of their adverse effects and potentially fatal outcomes.…”
mentioning
confidence: 99%
“…Epidemiological studies from Turkey have reported that children constitute one-third of patients admitted to the emergency department due to poisoning and that more than half of these are children younger than 6 years with accidental intoxications. One of the most common sources of intoxication, after multiple drug intake and corrosive poisoning, is tricyclic antidepressants (TCAs) 2–5 …”
mentioning
confidence: 99%